Long-term effects of exercise interventions on physical activity in breast cancer patients: a systematic review and meta-analysis of randomized controlled trials - Goldschmidt, Siri; Schmidt, Martina; Steindorf, Karen (Supportive care in cancer, 2023)
Benefits of exercise interventions for cancer patients are well established. This systematic review aimed to investigate the sustainability of exercise interventions with respect to physical activity behaviour of breast cancer patients in the longer term.
Gesehen am 16.03.2023